Dissecting the effects of childhood bullying on family formation - Loh, Chuan Jian (Nanyang Technological University, 2023)
32% of children aged 13 to 15 are bullied at least once per month. This paper studies the effects of childhood bullying on family formation, including the effect of bullying on the decision to marry (H1), marriage timing (H2) and childbearing decisions (H3), along with the role of bullying-induced emotions on marriage timing (H4). A longitudinal study of 17,415 individuals over 55 years in the UK was used for analysis through linear and probit panel regressions. Specifically, multiple control variables and the use of fixed effects analysis across time and region accounted for potential confounders contributing to exogeneity. Overall, childhood bullying does not have a statistically significant relationship with marriage decisions. However, victims marry 0.49 years earlier and are 2.87% more likely to have children. Interestingly, we find a differential effect on gender where males experiencing bullying were 1.06% less likely to be married on average, ceteris paribus. Our findings dissect the relationship between bullying, emotions, marriage and childbearing. These insights may assist policymakers in implementing interventionist strategies to address declining fertility rates and improve social and human capital.